2018
DOI: 10.3389/fneur.2018.01039
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Wearable-Sensor-Derived Measures of Physical Activity in Wheelchair-Dependent Spinal Cord Injured Patients

Abstract: Physical activity (PA) has been shown to have a positive influence on functional recovery in patients after a spinal cord injury (SCI). Hence, it can act as a confounder in clinical intervention studies. Wearable sensors are used to quantify PA in various neurological conditions. However, there is a lack of knowledge about the inter-day reliability of PA measures. The objective of this study was to investigate the single-day reliability of various PA measures in patients with a SCI and to propose recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 58 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…Five wearable ZurichMOVE 1 IMU sensors (Schneider et al, 2018) were used for gait monitoring, with one attached to each ankle, and each wrist, as well as the chest, using kinesiology tape (Figure 1), to monitor axial acceleration a (t) and angular velocity ω (t) for each segment. The global X-axis was defined as the vertical axis, the global Y-axis as the anteroposterior axis and the global Z-axis as the lateral axis.…”
Section: Sensor Placementmentioning
confidence: 99%
“…Five wearable ZurichMOVE 1 IMU sensors (Schneider et al, 2018) were used for gait monitoring, with one attached to each ankle, and each wrist, as well as the chest, using kinesiology tape (Figure 1), to monitor axial acceleration a (t) and angular velocity ω (t) for each segment. The global X-axis was defined as the vertical axis, the global Y-axis as the anteroposterior axis and the global Z-axis as the lateral axis.…”
Section: Sensor Placementmentioning
confidence: 99%
“…The difference between the weekday & weekend and only weekday analysis is primarily due to a difference in arm use intensity levels during weekdays versus weekends. One other study has investigated the reliability of wheelchair-based metrics from wrist-worn accelerometry data for individuals with SCI who use MWCs [ 26 ]. The metrics included measures of physical activity intensity, wheeling quantity, and movement quality from data collected during in- and out-patient settings.…”
Section: Discussionmentioning
confidence: 99%
“…The metrics included measures of physical activity intensity, wheeling quantity, and movement quality from data collected during in- and out-patient settings. Their results suggest that four days of data are needed for good reliability of movement quality and three days are required for most other metrics in the out-patient setting [ 26 ]. Schneider et al found no difference between weekdays and weekends in wheelchair distance traveled [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations